Chicken serologic response to Salmonella enterica serotype Typhimurium assessed by Elisa - Oliveira, GH [UNESP]; Berchieri Jr, A [UNESP]; Montassier, Helio Jose [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2006)
This study evaluated two enzyme-linked immunosorbent assays (ELISA) in the detection of chicken serologic response against Salmonella enterica sorotype Typhimurium. The assays have used as detecting antigen the soluble bacterial proteins of a non-flagellated strain of Salmonella Typhimurium (AgTM), and antibody conjugated to peroxidase or alkaline phosphatase. According to the results, optimal dilutions of antigen (concentration 5.49 mg/mL) and serum samples in both assays were 1:20,000 and 1:1,000, respectively. In such conditions, the ELISA/AgTM was able to detect serological response to Salmonella Typhimurium. Cross-reactions to Salmonella serotypes Gallinarum and Pullorum were seen, but not with other serotypes such as Enteritidis.
Keywords: Chicken; ELISA; enzyme; Salmonella sp; Serology